Assessment of Agricultural Wastes in the Removal of Hexavalent Chromium - Andal , N. Muthulakshmi; Charulatha, S. (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
The present study highlights the assessment of Agricultural Wastes in the Removal of Hexavalent Chromium. Hexavalent chromium is a major pollutant produced by a variety of industrial processes. Adsorbents derived from waste agricultural byproducts have been used to remove hexavalent chromium. Study mainly focused on comparing certain agro based products for the chelation of Cr(VI) ions. An extensive list of agricultural based products such as Coconut Coir, Prunus amygdalus, Cissus quadrangularis, Soapnut Acacia, Justicia adhatoda, Bhringraj, Aerva lanata, Trianthema portulacastrum, Tephrosia purpurea, Solanum nigrum, Datura metel, Cleome viscose, Asparagus racemosus employed for Cr(VI) trapping from aqueous solutions and the discharged industrial effluents are reviewed in this work. Chemically altered materials have greater adsorption capacities and are therefore used to modify the reported materials in the research articles in particular ways. For further investigation into the extensive use of the used materials, the results reported by the authors have been compared and summarized. The comparative study on biosorbents proves that they possess high potential in full- scale for the removal of toxic metal ions.